Sports as a field of social mode of life: an experience in handball - Dourivaldo Teixeira (Journal of Physical Education (Maringá), 2008)
This study deals with an investigation on the level of 12-to-13-year-old male students-athletes’ sociomotive learning when submitted for comparison to the following methodologies: functional/integrative and traditional. Its objective was eventually to point out the best methodological option for sports learning and especially to verify and compare the sociomotive interaction level of the practitioners submitted to these methodologies. The results led to the conclusion that handball is an important sport for social mode of life and that the functional/integrative methodology offered a better possibility of social interaction than the traditional method in favoring sociomotive learning of the practitioners.